1970
DOI: 10.3329/jdmc.v18i1.6310
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis C Virus among Health Care Workers

Abstract: Context: Hepatitis C virus is one of the leading causes of liver disease and represents a major public health problem. It is a common cause of cirrhosis and hepatocellular carcinoma (HCC) as well as the most common reason for liver transplantation. Methods: A cross sectional study was carried out during the period of April 2007 to April 2008 among health care workers including phlebotomists, dialysis staffs and laboratory personnel handling blood and blood products. Total 200 health care workers from phlebotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In our study the prevalence of HCV was 1.17%.This is in concordance with Uddin et al, (2009) study. 12 Ganju et al, (2000) reported that the prevalence of HCV among healthcare workers was about 0-4%. Jindal et al, (2006) found that exposure to infected blood/blood products of patients of HCV infection in the form of accidental needle pricks, contact of cut skin surface with blood/blood products, improper disposal of infected medical waste, etc.…”
Section: Follow-up Studymentioning
confidence: 99%
“…In our study the prevalence of HCV was 1.17%.This is in concordance with Uddin et al, (2009) study. 12 Ganju et al, (2000) reported that the prevalence of HCV among healthcare workers was about 0-4%. Jindal et al, (2006) found that exposure to infected blood/blood products of patients of HCV infection in the form of accidental needle pricks, contact of cut skin surface with blood/blood products, improper disposal of infected medical waste, etc.…”
Section: Follow-up Studymentioning
confidence: 99%
“…HCV prevalence in Europe is 1.03%, Africa 5.3%, Mediterranian region 4.6%, Western pacific region 3.9% and South east Asia 2,13% 2 . In Bangladesh prevalence is 1% among health care workers 3 . About 55% to 85% of acutely infected persons ultimately lead to chronic infection 4 .…”
mentioning
confidence: 99%